(untitled) (Global Journal of Science Frontier Research, 2012)
This study examined the demand for frog meat in Ondo State, Nigeria. A random sampling technique was used to select 100 consumers of frog meat. The tools of analysis were descriptive statistics like percentage, frequency distribution and tables; Regression analysis was also used to estimate the demand for frog meat and determine factors that influences same. The result of the analysis showed that 74% of the respondents are above 40 years of age, 82% married, 67% had family size of at least 6 and 76% claimed that frog meat is generally acceptable. The demand functions shows that the independent variables specified in the model accounted for 58.8% of the variability observed in the demand for frog meat. Furthermore, age (x1), family size (x4) and level of acceptability (x8) were significant at 5% level, implying that they have important implications for the demand for frog in the study area. This study recommends the heed for the populace to be educated on importance and nutritional implications of the consumption of frog meat.